Spatial analysis and identification of suitable landing zones for aerial evacuation from the congested urban areas - Smailbegovic, Amer; Mahmutovic, Vahidin (Crisis Management Days, 2024)
Introduction: According to the latest estimates to 2023, about half of the Bosnia and Herzegovina population lives in concentrated urban areas (CEIC, 2023). Considering congested or inadequate road communications in the urban areas, unfavorable steep relief and other potential obstacles, the issue of urgent evacuation becomes problematic, especially in the case of a widespread emergency. Using the municipal areas of Sarajevo and Banja Luka as the sites with a high level of risk for natural disasters and/or incidents caused by the human factor, we have attempted to identify the potential zones from which it would be possible to organize and carry out the aerial evacuation of the affected population on a larger scale than previously analyzed (Smailbegovic & Mahmutovic, 2024). Methodology: Considering the potential causes and epicenters of disasters (earthquake, flood, industrial incidents, terrorism), population density, road infrastructure, geomorphological and other terrain and land cover elements, we made a selection of potential aerial evacuation points from the congested urban areas (Erskine et al. 2022). The analysis consisted of two elements: 1. a semi-quantitative automated, integrative spatial-matching model that analyzes the available geospatial data (e.g. population, proximity to the epicenter, terrain coverage) and assigns an overall suitability score for the particular landing site (Walter and Fritsch, 1999; Mertova, 2021) and 2. qualitative-expert evaluation of selected landing sites by the pilots qualified and trained for evacuation from such complex areas (Scherer at al. 2010). The intent was to filter the various levels of geospatial data using the automated method and qualify or disqualify the potential sites by its overall matching score (i.e. open space, obstructions, accessibility, spatial correlation). The qualified areas were evaluated by the expert pilot and assessed upon experience and suitability of sustaining the evacuation operations with the available equipment. Results: The results of the bi-level analysis suggest that the urban areas of Sarajevo and Banja Luka each have at least three ideal and five acceptable locations which could sustain large-scale emergency evacuation of affected residents. The ideal areas have exhibited the automated matched score of at least 90 percent and unanimous approval from the three expert aviators. The acceptable landing zones have scored at least 75 percent match and two thirds approval from the expert aviators. The choice of locations and their viability depends on the type of potential disaster, but according to the available data, it is realistic to expect that the selected locations would withstand and remain partially usable in the majority of possible emergencies. Concluding remarks: Given congestion of urban areas and lack of overall planning towards evacuation in an emergency, it is encouraging that suitable aerial evacuation sites exist in the major municipal areas of Bosnia and Herzegovina even though they were not planned for that exact purpose. The combined automated and expert-validated method shows potential in determining other suitable landing zones for aerial evacuation in the complex terrain.